I'm Positive, But I'm Negative: Competing Voices in Informed Consent and Implications for HIV Vaccine Trials. (April 2015) - Rautenbach, Clinton; Lindegger, Graham; Slack, Catherine; Wallace, Melissa; Newman, Peter
HIV vaccine trials (HVTs) are ethically complex, and sound informed consent processes should facilitate optimal decision-making for participants. This study aimed to explore representations of critical HVT-related concepts to enhance the consent process. Four focus group discussions were conducted with participants from key constituencies at a South African HVT site. Thematic analysis was employed to identify representations of key HVT-related concepts. The findings suggest that (potential) participants may negotiate multiple, competing versions of HVT-related concepts in a somewhat unrecognized process, which may have significant implications for the consent process. Stakeholders involved in consent and engagement activities at sites should be assisted to elicit, engage, and resolve competing representations of HVT-related concepts. More empirical research is needed to explore how such stakeholders address competing representations in their interactions with potential participants.